2023
DOI: 10.3201/eid2902.221750
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Monkeypox Virus Transmission to Healthcare Worker, California, USA, 2022

Abstract: Risk for transmission of monkeypox virus (MPXV) (clade IIb) to healthcare workers (HCWs) is low. Although many cases have been reported among HCW, only a few have been occupationally acquired. We report a case of non–needle stick MPXV transmission to an HCW in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Because PCR is highly sensitive, a positive result can be obtained when samples are collected by using this method. Third, although tecovirimat is generally recommended for patients with severe mpox or high risk of dissemination ( 10 ), the drug was administered to our patient, who had localized infection, to prevent disease progression; prompt administration of tecovirimat might be necessary to maximize effectiveness. Most patients with mpox report extreme pain in the affected area.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because PCR is highly sensitive, a positive result can be obtained when samples are collected by using this method. Third, although tecovirimat is generally recommended for patients with severe mpox or high risk of dissemination ( 10 ), the drug was administered to our patient, who had localized infection, to prevent disease progression; prompt administration of tecovirimat might be necessary to maximize effectiveness. Most patients with mpox report extreme pain in the affected area.…”
Section: Discussionmentioning
confidence: 98%
“…Lesions developed on the hands and wrists of the other 2 HCWs, and the mode of transmission was likely fomite contact with bare skin. The HCW from California ( 10 ) was immunocompromised and worked in a clinic where patients with mpox regularly visited; unrecognized exposure and spread might have occurred through respiratory droplets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these reassuring previous findings, reports of HCP occupational infections are emerging monthly since July 2022 9 , 10 , 11 , 12 , 13 , 14 . Here, we characterized a case of nosocomial transmission of MPOX virus using molecular typing, and review the current literature.…”
Section: Introductionmentioning
confidence: 89%
“…60,61,67,72,78,79,84,86,88,89,92,94,97,98,104,109,111,112,113,114,115,122,126), 8 studies from North America(17,46,64,70, 85,93,106,107), and 3 studies from South America(30,71,103). 11 studies reported on cases acquired from multiple world regions(16,34,41,59,63,65,87,91,110,117,119), and 6 studies did not report the country of infection acquisition(68,75,96,105,108,118)....…”
mentioning
confidence: 99%